Actinomycosis presenting as a parotid tumor - Sittitrai P. (2014)
Actinomycosis of the parotid gland is a rare chronic infection and can present with a slow-growing mass mimicking a tumor. The authors report five cases of parotid actinomycosis. All patients presented as having enlarging masses at the parotid area for 2-6 months without a history of obvious dental infection, trauma, or immunocompromised condition. Retrograde bacterial spread from colonization in the oral cavity via Stensen's duct is the possible pathophysiology. The diagnosis was made histopathologically by fine needle aspiration biopsy (FNAB). Treatment consisted of 1.5 months of intravenous penicillin, followed by 4.5 months of oral penicillin, with excellent results. © 2011 Elsevier Ireland Ltd. All rights reserved.